The impact of the bankruptcies of SVB, SBNY and FCB on chosen cryptocurrencies - Spurný, David; de Batz de Trenquelléon, Laure Sabine Marie; Taušer, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
Since cryptocurrencies and their interconnectedness with traditional banking institution is still a relatively novel problematic, the aim of this diploma thesis is to assess the impact of a recent collapse of Silicon Valley Bank, New York's Signature Bank and First Republic Bank on five cryptocurrencies selected by their respective market cap. Policies such as quantitative easing with its impact on behavior of institutions and investors and also outcomes of recent FED decisions are assessed first. Legislation acts like Frank-Dodd act, Economic Growth Relief, and Consumer Protection Act and their influence over the banking sector, investors and emergence of financial technologies are examined as well. The emergence of financial technologies companies and startups and conclusions of those new technologies over traditional financial institutions is assessed after. Finally, the rise of cryptocurrencies will be evaluated with all that was aforementioned to understand the place cryptocurrencies have in economy and contemporary banking and how they can be impacted by macroeconomic factors. As mentioned, the main research focus of the thesis is to study the immediate impact of the bankruptcy of banks mentioned above in the region of USA on cryptocurrency market with future implications. Event study is used as a main methodology, combined with a review of existing literature. The thesis should contribute to research on cryptocurrencies and their role in the economy during banking crises.
Vedoucí práce: Laure Sabine Marie de Batz de Trenquelléon
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses